Identifikasi Penggunaan Kata-kata Umpatan Representasi Hewan Dikalangan Generasi Z Kota Bandung - Iqbal, Ryanto Maulana; Pamungkas, Indra N. A; Rozaq, Miftahul (eProceedings of Management, 2024)
This research is motivated by the use of swear words as a communication culture among Generation Z. Thisphenomenon is often accepted within their environment. The swear words are predominantly represented by animalrelated terms. The purpose of this study is to examine the phenomenon of using animal representative swear words,specifically the word